Penerapan Pembelajaran Kooperatif Reciprocal Teaching Berbasis Lesson Study untuk Meningkatkan Kemampuan Metakognitif Mahasiswa IKIP Budi Utomo Malang - Dwi Candra Setiawan; Erfitra Rezqi Prasmala; Dyah Ayu Widya Ningrum (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2016)
The quality of education in Indonesia still needs to be improved both in human resources and components in the learning process . Improving the quality of education is very important because the quality of a nation is determined by the education factor . Education in Indonesia is still emphasis on cognitive learning outcomes , so the ability of other students as metacognitive less empowered . Those problems need to be addressed , either by applying learning strategies Reciprocal Teaching ( RT ) based Lesson Study . Application of Lesson Study based learning is expected to empower metacognitive skills of learners .The purpose of this study is to explain the improvement of the learning process with regard metacognitive skills of students after learning Reciprocal teaching strategies implemented based Lesson Study. This study used two cycles with each cycle has four stages . These stages form a spiral cycle which includes 1 ) planning, 2 ) granting the action , 3 ) observation , and 4 ) reflection . Lesson Study is an improvement of learning undertaken collaboratively by measures planning ( Plan) , implementation of the plan learning in the classroom ( Do) , and reflection activities that discussions about things that happen in the learning process in the classroom ( See) . Lesson Study activities aimed at improving the quality of learning that has three stages , namely Plan, Do and See. Samples used in this research is student of Class C in 2014 as many as 45 people . The results showed learning strategies Reciprocal Teaching ( RT ) based Lesson Study can improve student metacognitive ability IKIP Budi Utomo Malang.